THEORY AND PRACTICE OF LITERARY TRANSLATION: THE SITUATION IN UZBEKISTAN - Zarina Nailevna Nabiulina (Western European Studies, 2025)
Literary translation plays a crucial role in the cultural and intellectual exchange between nations, facilitating the dissemination of literary works across linguistic and geographical boundaries. In Uzbekistan, the field of literary translation has evolved over time, reflecting historical, linguistic, and socio-political influences. This study explores the theory and practice of literary translation in Uzbekistan, analyzing its current state, challenges, and prospects. The research examines key theoretical approaches to translation, the role of translators in preserving cultural identity, and the difficulties faced in rendering literary texts from Uzbek into other languages and vice versa. By investigating the balance between fidelity and creativity in translation, the study highlights the impact of linguistic structures, idiomatic expressions, and cultural nuances on translated literature. The findings contribute to a better understanding of Uzbekistan’s literary translation landscape and its implications for the global literary community.
Keywords: Literary translation; translation theory; Uzbek literature